Kyrgyz Republic : Staff Report for the 2001 Article IV Consultation and Request for Three-Year Arrangement Under the Poverty Reduction and Growth Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Executive Directors commend the government for their achievements in macroeconomic stabilization. Continuing growth, low inflation, and stability in the foreign exchange market provide a solid foundation for the new program. Renewed effort to strengthen tax administration is required. Success in fiscal consolidation depends on streamlining public investment. The National Bank of the Kyrgyz Republic (NBKR) has to balance between maintaining low inflation and satisfying the economy's liquidity needs. A continuation of the tight monetary policy is needed. The Kyrgyz Republic's external debt is a serious problem.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet